Understanding the Dynamics of Tourist Experience through a Qualitative Lens: A Case Study Approach in Indonesia - Sri Budi Cantika Yuli (Global Review of Tourism and Social Sciences, 2024)
This qualitative study explores the dynamics of tourist experiences in Indonesia, focusing on how cultural, environmental, and service-related factors shape tourist satisfaction and retention. Through in-depth interviews and thematic analysis, the research uncovers insights into the perceptions of both domestic and international tourists, offering practical recommendations for enhancing tourism services in Indonesia. Tourism is one of the main drivers of Indonesia’s economy, making it essential to understand tourist perceptions to promote sustainability and growth. The paper delves into multiple aspects of tourism, from cultural engagement to service quality, analyzing how these factors interact and contribute to the overall tourist experience. The results highlight key areas for improvement in the tourism sector and offer strategies for enhancing visitors' experience in Indonesia.